Solvent Vapour Induced Film Formation of PS/AgNPs Composites Using Spectroscopic Techniques - Akaoglu, Can; Ugur, Saziye (Journal of Coating Science and Technology, 2018)
In this work, pyrene labeled polystyrene (PS) latex dispersions and silver nanoparticles (AgNPs) were mixed at different weight ratios of AgNPS in the range of 0-50 wt%. Powder (PS/AgNPs) films were prepared on glass substrates from these mixtures by the drop-casting method at room temperature. The fast transient ﬂuorescence (FTRF) technique was used to monitor the film formation process of PS/AgNPs composites by measuring the ﬂuorescence lifetimes of pyrene during vapour exposure. It was observed that pyrene lifetimes decreased as vapour exposure time, t increased obeying Stern–Volmer kinetic. The optical transmission (UVV) experiments showed that the transparency of the films decreased with increasing AgNPs content. Transparent films were produced for the composites with 0 to 20 wt % of AgNPs content. The Prager–Tirrel model was employed to FTRF and UVV data to obtain back-and-forth frequencies, ν, of the reptating PS chains during vapour induced ﬁlm formation process and polymer interdiffusion was found to obey a t1/2 law. Although the conductivity increased by 3 orders of magnitude with increasing AgNPs content, the composites behaved like an insulator. The morphology of composite films also progressively changed during vapour exposure and affected by AgNPs content.